Implementasi Kebijakan Untuk Mengatasi Penyalahgunaan Narkotika di Kalangan Remaja - Firmanyanto; Badu, Lisnawaty W.; Mantalie, Avelia Rahmah Y. (Journal Evidence Of Law, 2025)
This study aims to analyze the efforts of the Gorontalo Provincial National Narcotics Agency (BNNP Gorontalo) in combating drug abuse and illegal drugs among teenagers. The background of this study is based on the increasing number of drug abuse cases among teenagers, which has become a serious challenge for the government and society, especially in Gorontalo Province. This study employs an empirical method with a qualitative approach, where primary data was obtained through in-depth interviews with investigators and counselors from BNNP Gorontalo, as well as direct observation of program implementation in the field. Secondary data was collected from documents, reports, literature, and relevant laws and regulations. Data analysis was conducted qualitatively by linking field findings with existing theories and concepts. The results of the study indicate that BNNP Gorontalo has implemented various strategies, such as inter-agency cooperation, border surveillance, and the implementation of the Community Education and Empowerment Program (P2M) in schools that focus on strengthening character and family resilience. Prevention efforts are also supported by education and awareness campaigns involving families, schools, and the community. However, the effectiveness of rehabilitation programs still faces challenges, primarily due to limited information about adolescents involved in drug use, as families and schools are reluctant to report such cases. The success of the program heavily depends on close collaboration and open communication among all relevant parties. This study recommends the need to enhance synergy between families, schools, and the community, as well as strengthening structured education and rehabilitation programs to reduce drug abuse rates among adolescents in Gorontalo Province.